2008
DOI: 10.1111/j.1756-1221.2008.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Happily Ever After: Integrating Language and Literature through Technology?

Abstract: This article describes a fourth‐year German course on fairy tales that focuses on the integration of academic content with linguistic skills through technology‐enhanced course modules. Situated in the discussion of the language‐literature gap and the benefits of computer‐assisted language learning, the proposed online course modules may prove appropriate in other German classes, thereby providing language educators with specific examples to help integrate the teaching of language and literature through online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Some program directors believe that face-to-face class-time is used inefficiently and that with the help of online technologies the classroom could be more efficiently used for a focus on communication NCAT, 2001;Sanders, 2005). In upper division content courses, a blended format or a technology-enhanced format was suggested as a way to provide an additional, necessary, and desired focus on form that content instruction often lacks (Kraemer, 2008b;Kraemer, 2008c;Zyzik & Polio, 2008). In addition, technology-enhanced instruction is also seen as an environment that offers immediate feedback opportunities (Blake, 2007;Chapelle, 2007;.…”
Section: Improvement Of Instructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some program directors believe that face-to-face class-time is used inefficiently and that with the help of online technologies the classroom could be more efficiently used for a focus on communication NCAT, 2001;Sanders, 2005). In upper division content courses, a blended format or a technology-enhanced format was suggested as a way to provide an additional, necessary, and desired focus on form that content instruction often lacks (Kraemer, 2008b;Kraemer, 2008c;Zyzik & Polio, 2008). In addition, technology-enhanced instruction is also seen as an environment that offers immediate feedback opportunities (Blake, 2007;Chapelle, 2007;.…”
Section: Improvement Of Instructionmentioning
confidence: 99%
“…Including similar technology tools for similar task types at different levels can improve vertical articulation. In addition, technology allows a supplementary content focus in the lower level courses and a supplementary language focus in the upper level courses (Kraemer, 2008c). In addition, Sanders (2005) reported that the hybridization of the first year Spanish program resulted in better horizontal articulation, i.e., articulation across sections.…”
Section: Articulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a consideration of the role of new technologies in language-literature instruction may also shed light on the development of FL literacy and advanced language abilities. A handful of studies have provided empirical support for the effectiveness of hybrid learning modules (Kraemer, 2008a(Kraemer, , 2008b, electronic glosses and online dictionaries (Johnson, 2010), and collaborative online writing practice (Grossman, 2009) for integrating language and content and increasing student success and interest in reading literature. Future research might explore these and other technologies, such as computer-mediated communication with target language cultures to create communities of learning, or online collaborative text applications (e.g., eComma) to analyze and interpret literature.…”
Section: Resultsmentioning
confidence: 99%
“…Student‐centered, active learning was the focus of Kraemer's () approach to integrating linguistic development, literary analysis, and cultural learning in a German fairy tale course. Technology was used extensively to explore course content through Webquests, facilitate interaction through threaded discussions and blogs, scaffold learning through pre‐ and post‐reading tasks, and conduct assessments such as projects and self‐evaluations.…”
Section: Integrating Language and Literary‐cultural Content In The Admentioning
confidence: 99%